Comparison of enzyme activities with diagnostic potential in healthy and root (wilt) diseased coconut palms, differing in cultivars and growth stages - Chaturvedi, V.K.; Srinivasan, N.; Sasikala, M.; Jacob, P.M.; Rajeev, G. (Journal of Plantation Crops, 2012)
Activities of superoxide dismutase (SOD), succinic dehydrogenase (SucDH), exochitinase (Cht) and 1, 4 β-glucanase (Glucn) were quantified to assess their diagnostic potential for detection of, or their role in imparting tolerance against, root (wilt) disease (RWD). The enzymes were determined in healthy and infected palms of contrasting coconut cultivars - Chowghat Green Dwarf (CGD) and/or Malayan Green Dwarf (MGD) tolerant and West Coast Tall (WCT) - susceptible, in the adult palms and in some at the seedling growth stage. Healthy and RWD plants differed little and that too inconsistently with respect to the activities, specific activities and soluble protein content of all the 4 enzymes, offering no diagnostic potential, in the three cultivars. However, cultivars and growth stage differences for enzyme activities were found to be significant for some enzymes. The RWD tolerant cultivar CGD (10-year old palms) had higher SOD and SucDH activity, higher soluble protein in the SOD and SucDH extract and lesser SOD specific activity than the RWD susceptible cultivar WCT (40-year old palms). The RWD tolerant cultivar MGD had lesser SOD activity than WCT in the seedling stage, lesser SOD specific activity in the adult stage (15-year old palms), higher SucDH activity and specific activity, higher soluble protein in the SOD extract, but lesser soluble protein in the Cht extract than 40-year old WCT adult palms. Seedlings of WCT and MGD had higher SOD activity than their adult plants. Seedlings of WCT and CGD had higher soluble protein in SOD extract than their adult plants. Seedlings of CGD had higher soluble protein in SucDH extract than its adult plants. Metabolic differences in enzyme activities indicated that the cultivars CGD followed by MGD and the seedling stage or younger plants seem to have a better capacity in resisting the effects of root (wilt) disease.